Restoration of semi-industrial glazed ceramic tiles by re-firing - Chaban, A. (2015)
Semi-industrial glazed ceramic tiles lining urban façades represent a rich heritage asset of Portuguese cities and in particular of Lisbon. However, still a sizeable part of them is being continuously lost. Whenever the façade tiles are decayed, they are usually merely removed and replaced by newly manufactured ones. Following preliminary tests done at LNEC in 2012, we introduce in this communication re-firing as an alternative to simple disposal of damaged original tiles. We assess the technique as a technological option for the restoration of crazed and spalled tiles. The re-firings are applied at different heatworks and temperatures and the effects of all tests are studied by visual, microscopic observation and through the glaze resistance to a pull-off. The effect of continuous serviceability of the re-fired tiles is assessed through accelerated ageing tests. The domain of application of the technique and the shortcomings detected are presented and discussed in this communication. Dwelling on a new ground, we present the initial results on which further research in this field can be based.